Kako napisati in objaviti znanstveni članek s področja menedžmenta - Meško, Maja (Revija za univerzalno odličnost, 2013)
Science is one of the most important human activities and is crucial for the development of society. Scientific research results should be presented to the public, which can be done through various publications. The article was written for graduate students and beginner researchers and presents steps for writing scientific papers. A well-written scientific paper consists of essential parts, i.e. appropriate structure, which in presented in this paper. The authors of this article present tips and useful advice when writing and publishing scientific papers in the field of management.
Keywords: članki; management; objavljanje; pisanje; raziskovalno delo; scientific method; writing; znanstveni časopisi; znanstveni sestavki; znanstveno raziskovanje